Integrated pressure–temperature–time constraints for the Tso Morari dome (Northwest India): implications for the burial and exhumation path of UHP units in the western Himalaya. (4th March 2013) - St‐Onge, M. R.; Rayner, N.; Palin, R. M.; Searle, M. P.; Waters, D. J.
Abstract Northward subduction of the leading edge of the Indian continental margin to depths greater than 100 km during the early Eocene resulted in high‐pressure (HP) quartz‐eclogite to ultrahigh‐pressure (UHP) coesite–eclogite metamorphism at Tso Morari, Ladakh Himalaya, India. Integrated pressure–temperature–time determinations within petrographically well‐constrained settings for zircon‐ and/or monazite‐bearing assemblages in mafic eclogite boudins and host aluminous gneisses at Tso Morari uniquely document segments of both the prograde burial and retrograde exhumation path for HP/UHP units in this portion of the western Himalaya. Poikiloblastic cores and inclusion‐poor rims of compositionally zoned garnet in mafic eclogite were utilized with entrapped inclusions and matrix minerals for thermobarometric calculations and isochemical phase diagram construction, the latter thermodynamic modelling performed with and without the consideration of cation fractionation into garnet during prograde metamorphism. Analysis of the garnet cores document (M1) conditions of 21.5 ± 1.5 kbar and 535 ± 15 °C during early garnet growth and re‐equilibration. Sensitive high resolution ion microprobe (SHRIMP) U–Pb analysis of zircon inclusions in garnet cores yields a maximum age determination of 58.0 ± 2.2 Ma for M1. Peak HP/UHP (M2) conditions are constrained at 25.5–27.5 kbar and 630–645 °C using the assemblage garnet rim–omphacite–rutile–phengite–lawsonite–talc–quartz (coesite), with mineral compositional data and regional considerations consistent with the upper P–T bracket. A SHRIMP U–Pb age determination of 50.8 ± 1.4 Ma for HP/UHP metamorphism is given by M2 zircons analysed in the eclogitic matrix and that are encased in the garnet rim. Two garnet‐bearing assemblages from the Puga gneiss (host to the mafic eclogites) were utilized to constrain the subsequent decompression path. A non‐fractionated isochemical phase diagram for the assemblage phengite–garnet–biotite–plagioclase–quartz–melt documents a restricted (M3) P–T stability field centred on 12.5 ± 0.5 kbar and 690 ± 25 °C. A second non‐fractionated isochemical phase diagram calculated for the lower pressure assemblage garnet–cordierite–sillimanite–biotite–plagioclase–quartz–melt (M4) documents a narrow P–T stability field ranging between 7–8.4 kbar and 705–755 °C, which is consistent with independent multiequilibria P–T determinations. Th–Pb SHRIMP dating of monazite cores surrounded by allanite rims is interpreted to constrain the timing of the M4 equilibration to 45.3 ± 1.1 Ma. Coherently linking metamorphic conditions with petrographically constrained ages at Tso Morari provides an integrated context within which previously published petrological or geochronological results can be evaluated. The new composite path is similar to those published for the Kaghan UHP locality in northern Pakistan, although the calculated 12‐mm a−1 rate of post‐pressure peak decompression at Tso Morari would appear less extreme.